Influence of dispersion of fibrillated cellulose on the reinforcement of coated papers - Sanchez-Salvador, Jose Luis (2023)
The use of cellulose micro/nanofibrils (CMNFs) as reinforcement paper additive at industrial scale is delayed due to inconsistent results, suggesting a lack of proper consideration of some key parameters. The high influence of fibrillated nanocellulose dispersion has been recently identified as a key parameter for paper bulk reinforcement but it has not been studied for surface coating applications yet. This paper studies the effect of CMNF dispersion degree prior to their addition and during mixing with starch on the reinforcement of paper by coating. Results show that this effect depends on the type of CMNFs since it is related to the surface interactions. For a given formulation, a correlation is observed between the CMNF dispersion and the CMNF/starch mixing agitation with the rheology of the coating formulation which highly affects the paper properties. The optimal dispersion degree is different for each nanocellulose, but the best mechanical properties were always achieved at the lowest viscosity of the coating formulation. In general, the initial state of the nanocellulose 3D network, influences the mixing and smooth application of the coating and affects the reinforcement effect. Therefore, the CMNF industrial implementation in coating formulations will be facilitated by the on-line control of formulations prior to their surface application.